The Lived Experience of Fanfiction Writers: Its Implications to Language Writing Skills (British Journal of Multidisciplinary and Advanced Studies, 2023)
Fanfiction writers have their own stories to tell as to why they were hooked into this form of writing.  These stories are relevant to the teaching of skills in writing.  Limited studies were found about the writing experiences of fanfiction writers.  This study explored the experiences with the overarching question: What is fanfiction writing as a lived experience among fanfiction writers? A transcendental phenomenology design was used to explore these experiences.  A three-phase phenomenological face-to-face interviews was conducted to collect the data.  Informal conversations and observations were also held.  Each interview was transcribed and sent back to each writer for checking and validation.  Actual fanfiction works were also observed.  From the data that were manually coded and categorized, three themes emerged from the eight categories such as outpouring and relief, transformation and connection, and development and motivation. Fanfiction writers write to express themselves as who they are including their feelings, their opinions, and their social interactions.  Fanfiction writing also enables them to develop their skill and passion for writing.  These experiences may help in skill-based teaching and learning especially in language classes.